2022
DOI: 10.1186/s40249-022-00989-7
|View full text |Cite
|
Sign up to set email alerts
|

Key immunity characteristics of diverse stages of brucellosis in rural population from Inner Mongolia, China

Abstract: Background Brucellosis poses a serious threat to human and animal health, particularly in developing countries such as China. The Inner Mongolia Autonomous Region is one of the most severely brucellosis-endemic provinces in China. Currently, the host immune responses functioning to control Brucella infection and development remain poorly understood. The aim of this study is to further clarify the key immunity characteristics of diverse stages of brucellosis in Inner Mongolia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Currently, there is a growing interest in studying immune protection mechanisms involving CD4 + and CD8 + T lymphocytes after Brucella infection ( 5 ). Recent studies have found that patients with brucellosis have a reduced proportion of CD4 + T lymphocytes in their peripheral blood but an increased proportion of CD8 + T lymphocytes ( 6 ). Some studies have suggested that Brucella infection disrupts the interaction between B lymphocytes and CD4 + T lymphocytes, thereby increasing the host’s susceptibility to Brucella ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a growing interest in studying immune protection mechanisms involving CD4 + and CD8 + T lymphocytes after Brucella infection ( 5 ). Recent studies have found that patients with brucellosis have a reduced proportion of CD4 + T lymphocytes in their peripheral blood but an increased proportion of CD8 + T lymphocytes ( 6 ). Some studies have suggested that Brucella infection disrupts the interaction between B lymphocytes and CD4 + T lymphocytes, thereby increasing the host’s susceptibility to Brucella ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of Brucella with TLR4 on host cells affects the induction of the immune response, and TLR4 plays a role in resistance to Brucella infection ( Campos et al., 2004 ; Dueñas et al., 2004 ; Copin et al., 2007 ; Martirosyan et al., 2012 ; Ma et al., 2015 ; Zhu et al., 2022 ). B. melitensis OMP25 interacted with ferritin heavy polypeptide 1 (FTH1) in human placenta trophoblastic cells (HPT−8) and led to the increase of the levels of TLR4 and inflammatory factors, suggesting that OMP25 serves an important role in intracellular parasitism of Brucella ( Zhang et al., 2022 ).…”
Section: Role Of Tlrs In Brucella Infectionmentioning
confidence: 99%
“…In recent years, the global incidence of brucellosis has risen annually, with 1.6 to 2.1 million new cases of human brucellosis being reported each year [2] . Brucellosis posed a serious threat to human and animal health and was a widespread problem in some developing countries [3] . In 2014, the reported incidence rate of brucellosis was 4.22/100,000 in China, marking the highest rate ever recorded [4] .…”
Section: Introductionmentioning
confidence: 99%